Using Platelet Parameters to Anticipate Morbidity and Mortality Among Preterm Neonates: A Retrospective Study - Go, Hayato; Ohto, Hitoshi; Nollet, Kenneth E.; Takano, Shunya; Kashiwabara, Nozomi; Chishiki, Mina; Maeda, Hajime; Imamura, Takashi; Kawasaki, Yukihiko; Momoi, Nobuo; Hosoya, Mitsuaki (Frontiers in Pediatrics, 2020)
Background: Platelets participate in many physiological and pathological functions and some platelet parameters predict adult diseases. However, few studies report whether platelet parameters may reflect neonatal disease and mortality in a large cohort. Objective: We aimed to investigate whether platelet parameters could predict bronchopulmonary dysplasia (BPD), necrotizing enterocolitis (NEC), intraventricular hemorrhage (IVH), and NICU mortality. Study Design and Methods: This retrospective cohort study examined records from 2006 to 2017 at the neonatal intensive care unit (NICU) of Fukushima Medical University Hospital. We retrospectively investigated platelet count, plateletcrit (PCT), mean platelet volume (MPV), and platelet distribution width (PDW) on the first day of life in preterm newborns born <32 weeks' gestation admitted to our NICU from 2006 to 2017. Receiver operating characteristic (ROC) and multiple regression analyses, along with Cox proportional hazard modeling, identified independent predictors of morbidities and mortality in preterm newborns. Results: Of 1,501 neonates admitted to our NICU, a total of 305 preterm newborns were included in this study. Gestational age, birth weight, and Apgar score were significantly lower in non-survivors than in survivors. Platelet count, PCT, PDW and PMI did not differ significantly between the two groups, whereas mean MPV in non-survivors was significantly higher than in survivors (10.5 fl vs. 10.0 fl, p = 0.001). Multivariate Cox hazard modeling showed that shorter GA [HR: 0.628, 95% CI: 0.464–0.840, p = 0.003], male sex [HR: 0.269, 95% CI: 0.113–0.640, p = 0.001], and MPV [HR: 1.469, 95% CI: 1.046–2.063, p = 0.026] independently predicted overall survival. Per receiver operating curve, an MPV threshold of 10.2 fl. MPV predicts prognosis in neonates with a sensitivity of 72.4% and a specificity of 58.6% (AUC = 0.685, 95% CI: 0.600–0.789, p = 0.001). Furthermore, multivariate analysis revealed that platelet parameters were not associated with BPD and NEC, whereas small for gestational age (SGA), Apgar score at 5 min, and low PCT were associated with intraventricular hemorrhage (IVH). Conclusion: This study demonstrates that low PCT predicts IVH, and MPV ≥ 10.2 fL correlates with mortality among infants born after <32 weeks' gestation.